2022
DOI: 10.18844/cjes.v17i8.7784
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perceptions on their competence and the benefits of inclusive education

Abstract: This study assessed the perceived teachers’ competence and benefits of inclusion to learners. There were 63 teachers who answered the survey questionnaires that assessed their perceived competence and benefits of inclusive education. They were identified using cluster sampling. The data gathered were treated using descriptive and inferential statistics. The results revealed that majority of them were in the age range of 33-42 years, had finished their master’s degree with specialisation not related to special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Meanwhile, Xue et al [19] found that teachers' inclusive learning competency is the key to the successful implementation of inclusive education. The significance of cultural, political, and human resource variables in the effective implementation of inclusive education has also been noted in other research [20]. Technology from today has also influenced every aspect of our existence, including inclusive education [21].…”
Section: Introductionmentioning
confidence: 65%
“…Meanwhile, Xue et al [19] found that teachers' inclusive learning competency is the key to the successful implementation of inclusive education. The significance of cultural, political, and human resource variables in the effective implementation of inclusive education has also been noted in other research [20]. Technology from today has also influenced every aspect of our existence, including inclusive education [21].…”
Section: Introductionmentioning
confidence: 65%
“…Education should provide the foundation of culture, which enables the realisation of the essential powers of the individual through a system of social experience transmission, a mechanism of social inheritance (Tenerife et al, 2022;Zhussupbekova et al, 2018). All this is possible only in the environment where one can express one's creativity.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Chaos gives way to Order in human perceptions of surrounding reality. An order is a system, an interconnection, a cause-and-effect relationship (Tenerife et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cebu City in the Philippines has special education (SPED) centers established by the Department of Education (DepEd), which aims to provide high-quality services and support to children with special needs [16]. Autism is one of the disorders that are catered to by these centers.…”
Section: Introductionmentioning
confidence: 99%